(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper proposes a method of personal identification based on the finger-vein patterns. A camera under the IR light transmission captures the finger hence capturing the finger vein patterns. We systematically develop a new approach for the finger vein feature extraction using Repeated Line tracking, Gabor filters and Matched Filter. The result after the combinations of these methods is more accurate than the results of the individual method. The aim of this paper is to investigate finger-vein technology.